Adalékok a magyar-német gazdasági kapcsolatok történetéhez, különös tekintettel a győri program megvalósítására - Szávai, Ferenc (Közép-Európai Közlemények, 2013)
In the Horthy era, in a period of economic development, the growth triggered by military economy gained importance. The Gyır army development programme was a part of this process; increasing the market and the exports for triggering growth instead of loans was a significant factor in this. The opportunity of Eastern foreign trade relations was replaced by Western (German) relations for this period based on mutual interests. The business relations between Daimler-Benz and Manfred Weiss mean intriguing additions to this and the study aims to reveal these issues.